2018
DOI: 10.4317/medoral.22610
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of the skeletal development in lateral cephalometric radiographs of HIV infected children ongoing Highly Active Antiretroviral Therapy

Abstract: BackgroundTo investigate the skeletal development of HIV infected children through a morphological analysis of the cervical vertebrae (CV) in lateral cephalometric radiographs.Material and MethodsThe sample consisted of 86 lateral cephalometric radiographs of male and female children aged between 6 and 14 years old. The radiographs were equally distributed in groups 1 (HIV infected children) and 2 (non-infected children, paired by sex and age). Two examiners analyzed the CV according to the method of Hassel an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In males with and without AI, the mean chronological age was 12.32 years in both groups. The scientific literature corroborates the inclusion of control groups in observational studies to enable comparable and more reliable outcomes 34 . Ratios above 1:2 (case:control) are recommended to detect potential alterations in the case groups with proper statistical support of the control group.…”
Section: Discussionmentioning
confidence: 90%
“…In males with and without AI, the mean chronological age was 12.32 years in both groups. The scientific literature corroborates the inclusion of control groups in observational studies to enable comparable and more reliable outcomes 34 . Ratios above 1:2 (case:control) are recommended to detect potential alterations in the case groups with proper statistical support of the control group.…”
Section: Discussionmentioning
confidence: 90%
“…Cervical vertebrae maturation was correlated with age in HIV-infected and uninfected children in a study and it was found that a weak correlation existed between cervical vertebrae maturation and age in HIV-infected children. The authors suggest caution in using cervical vertebrae maturation for predicting skeletal development in HIV-positive children for orthopaedic and orthodontic procedures [ 44 ].…”
Section: Reviewmentioning
confidence: 99%
“…Human Immunodeficiency Virus (HIV) or Acquired Immunodeficiency Syndrome (AIDS) was first detected in children in 1983 1 . According to the World Health Organization's (WHO) reports, the prevalence of HIV is increasing 2 . AIDS, which is caused by the development of HIV, makes the body vulnerable to infections and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In legal processes, determining age is important in terms of both punishment and the law 5 . Age identification can be correlated to physical, skeletal, and dental maturity as well as with the identification of corpses 2 . There are many methods for estimating age based on such important factors as the quality and quantity of the dead body remains, environmental conditions, cost, time, and the required equipment 6,7 .…”
Section: Introductionmentioning
confidence: 99%